Modification of rules in basketball: collective game description under-16 in attack - Marín, A. A.; Estévez López, F.; Cárdenas, D.; Piñar, M. I. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2013)
The aim of this study was to describe the characteristics of attack collective game of the boys 13-and-under competition. The variables studied were number of attack phases, type of each attack phase, duration of each attack phase, number of passes of each attack phase and number of players of each attack phase. The study sample comprised 1878 attack phases from the all six teams which played the boys 13-and-under regular competition for the season 2011/2012 in Granada (Spain), 72 players (age: M=12.56 years, SD=0.54) participated. This research did by means of observational methodology. The findings of the present study show an improvement in competition, adapting to the characteristics and needs of young players. Some aspects could be improved if it change further some of the values obtained in the variables analyzed.